Patterns of care in pancreatic cancer radiotherapy: impact of facility volume on outcomes - Rajan, Arvind; Gleeson, Elizabeth M.; Pham, Veronica; Goodman, Karyn A. (Frontiers in Oncology, 2025)
ObjectivesRadiotherapy (RT), particularly stereotactic body radiotherapy (SBRT), is a promising treatment for borderline resectable or locally advanced pancreatic cancer (PC). This study evaluated the association of RT facility volume with overall survival (OS) and examined patterns of care for patients with PC.MethodsA retrospective cohort study using National Cancer Database (NCDB) data (2004-2019) included 17,053 PC patients treated with RT, excluding those with metastatic or stage IV disease. RT facility volumes were categorized as low- (<10 cases/year), intermediate- (10–20 cases/year), and high-volume (>20 cases/year). Predictors of OS, including facility volume, RT type, and patient/treatment factors, were evaluated.ResultsAmong 17,053 patients (median age 67 years, 51.4% male), 17.6% received SBRT, and 27.1% were treated at high-volume centers. Treatment at high-volume centers (HR 0.863, p<0.001) and receiving SBRT (HR 0.869, p<0.001) were associated with improved OS. SBRT use increased from 8.5% (2004-2011) to 30% (2016-2019).ConclusionHigh-volume RT centers are associated with significantly better survival outcomes in PC patients, particularly those receiving SBRT. These findings emphasize the need to expand access to high-volume centers and develop standardized treatment protocols to improve care and outcomes for all patients.